Inflammation and Hypoxia Negatively Impact the Survival and Immunosuppressive Properties of Mesenchymal Stromal Cells In Vitro - Carmen Alexandra NECULACHI; Livia Ioana LETI; Alexandrina BURLACU; Mihai Bogdan PREDA (Sciendo, 2021)
Mesenchymal stromal cells (MSC) are nonhematopoietic cells with fibroblast-like morphology and multipotent capacity that are widely used in pre-clinical and clinical investigations. Unfortunately, the efficiency of MSC treatment is hindered by the poor survival rate after transplantation at the damaged tissue. The goal of this study was to investigate the fate of MSC exposed to various stimuli mimicking the in vivo microenvironment post transplantation. To this aim, murine bone marrow-derived MSC were stimulated with IFNgama and TNFalpha under low oxygen (hypoxia) or atmospheric (normoxia) conditions for 24 to 72 hours, in order to better mimic an ischemic injury. The results showed that MSC pre-stimulation with TNFalpha and IFNgama enhanced immunosuppressive pathways by over-expression of NOS2, IDO, COX2 and production of NO. However, MSC viability was affected by these two cytokines in dose-dependent and time-dependent manners. Besides, priming with TNFalpha and/or IFNgama under low oxygen concentrations revealed that significantly increased cell mortality rate and decreased NO production. Our data suggest that both hypoxia and inflammation could impact the cell survival after transplantation and reinforces the necessity of further investigations to better understand MSC behavior after transplantation in order to identify the MSC-based strategies with the highest therapeutic potential.